ax Reforms proposed by the International Monetary Fund within the framework of the October 2020 technical agreement: An analysis of Computable General Equilibrium for Ecuador - Maldonado, Katherine (2021)
The coronavirus pandemic (COVID-19) has caused the greatest health, human, economic and social crisis that the world has faced in the last century since World War II (ECLAC, 2020). The countries have found it necessary to adopt and reformulate public policies that counteract the effects generated by the health crisis. In this sense, fiscal policy has turned out to be a fundamental tool for countries and the international community to promote precise and timely measures aimed at economic reactivation and the well-being of society. For its part, the government of Ecuador in 2020, in addition to implementing fiscal policy measures, decided to request financing from the International Monetary Fund (IMF), with the aim of obtaining the necessary resources to face the crisis generated by COVID- 19. According to data from the Central Bank of Ecuador (ECB), the pandemic caused a contraction of GDP by 7.8%, an unemployment rate of 5.1%, a level of poverty and extreme poverty of 32.4% and 14, 9%, respectively; and losses of more than $ 16,381 million (ECB, 2021). To resume its relationship with the IMF, in October 2020, Ecuador signs a technical agreement, which proposes the reformulation of the Organic Code of Planning and Public Finance, and the modification to the Labor and Tax Code.